Students’ Perception of Online Learning in Pakistani Colleges - Nasir, Palwasha (Kashmir Journal of Academic Research and Development, 2025)
Online education has become an essential method of education in the world, which the COVID-19 pandemic has accelerated to an impressive rate. Online learning platforms in colleges rapidly gained acceptance in Pakistan though the experience of students is varied because of socio-economic, technological, and pedagogical problems. The paper will analyze the attitude of college learners towards online education in terms of accessibility, effectiveness, engagement, and satisfaction. Data were gathered through a qualitative design by gathering 300 students (including 25 interviews) in public and privatized colleges in Punjab and Sindh. Results show that although online learning is perceived to be both flexible and convenient by the students, they face major challenges such as poor internet connectivity, technical challenges, lack of increased interaction with faculty as well as lack of motivation. The research presents the need to enhance digital infrastructure, train students and faculty, and create interactive and student-centered online curricula as elements in increasing the efficiency of online learning in Pakistan.
Keywords: e-learning; online learning; higher education; student perception; Digital education; accessibility; engagement; blended learning; Pakistan